SPECIAL EDUCATION IN FIRST CHILDHOOD: A TEACHER'S PERSPECTIVE ON THE INCLUSION OF DEAF CHILDREN - Mauricio, Karina Courel; Amorim, Gabriely Cabestre [UNESP] (Univ Federal Mato Grosso Sul, 2018)
The National Policy on Special Education in the Perspective of Inclusive Education aims to access, participation and learning of students with disabilities in regular schools, aggregate subjects respecting their differences, cultures and historicity, being a modality that permeates all levels and stages, is also present in Early Childhood Education. The purpose of this study was to investigate the perspective of teachers regarding the care offered to infants and children deaf in the Early Childhood Education Centers (CEIs). For this purpose, a questionnaire on the subject was developed for 30 teachers, CEI employees of the municipal network of the Municipality of Sao Paulo, 30 women, aged between 21 and 50 years, from the Butanta region. The results of this research showed the opinion and concern of these teachers in relation to inclusion, the importance of their participation in the construction of a quality education, and their insecurity regarding their formation for an action that optimizes the potentialities of all subjects.
Keywords: Special Education; Inclusion; Childhood; Deafness; Teacher training